Union of Comoros : Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Union of Comoros. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Union of Comoros' Request for Disbursement Under the Rapid Credit Facility (RCF) and Purchase Under the Rapid Financing Instrument (RFI). Reflecting the large budgetary and external financing gaps arising from emergency assistance and reconstruction needs, the authorities are seeking financial assistance under the RCF and RFI exogenous shock windows. Comoros' qualification is based on urgent balance of payments needs following a severe natural disaster. The authorities shared staff's main policy recommendations. Efforts to address the cyclone's impact will need to focus on mobilizing external financing, creating fiscal space by containing the wage bill, and spending mobilized resources in a well-targeted and timely manner. The authorities plan to address financial sector weaknesses, including by finding a solution for the critical situation of the postal bank, closely monitoring nonperforming loans, and addressing obstacles in the judicial system to facilitate the use of collateral and promote lending.